2017
DOI: 10.1093/molehr/gax045
|View full text |Cite
|
Sign up to set email alerts
|

Growth regulation by estrogen in breast cancer 1 (GREB1) is a novel progesterone-responsive gene required for human endometrial stromal decidualization

Abstract: This research was funded in part by: a National Institutes of Health (NIH)/ National Institute of Child Health and Human Development (NICHD) grant (R00 HD080742) and Washington University School of Medicine start-up funds to R.K., an NIH/NICHD grant (RO1 HD-07857) to B.W.O.M., and a NIH/NICHD grant (R01 HD-042311) to J.P.L. The authors declare no conflicts of interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 45 publications
(48 reference statements)
4
42
0
Order By: Relevance
“…Interestingly, SRC-3 is reported to interact with growth regulation by estrogen in breast cancer 1 (GREB1) and increase estrogen-induced transcription in breast cancer cell line MCF-7 cells [ 39 ]. We found that GREB1 is transcriptionally activated by SRC-2 via the progesterone–PR axis in endometrium [ 40 ], and a novel fusion gene, GREB1-SRC-2 , was detected in uterine sarcoma [ 41 ]. These evidences point out that GREB1 may play a vital role in hormone-dependent cancers.…”
Section: Nuclear Receptor Coactivators In Hormone-dependent Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, SRC-3 is reported to interact with growth regulation by estrogen in breast cancer 1 (GREB1) and increase estrogen-induced transcription in breast cancer cell line MCF-7 cells [ 39 ]. We found that GREB1 is transcriptionally activated by SRC-2 via the progesterone–PR axis in endometrium [ 40 ], and a novel fusion gene, GREB1-SRC-2 , was detected in uterine sarcoma [ 41 ]. These evidences point out that GREB1 may play a vital role in hormone-dependent cancers.…”
Section: Nuclear Receptor Coactivators In Hormone-dependent Cancermentioning
confidence: 99%
“…GREB1 was first discovered in brain tissue [ 42 ] and later identified as an early estrogen-responsive gene in breast cancer [ 43 ]. The GREB1 gene is highly conserved across species and is expressed in many tissues, including the brain [ 42 ], mammary gland [ 43 ], ovary [ 16 ], prostate [ 44 ], and endometrium [ 40 ]. In humans, the GREB1 gene is located at 2p25.1, spans 108.68 kb, and contains 38 exons and 40 introns [ 43 , 45 ] ( Figure 2 ).…”
Section: Greb1 Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent study on an independent clinical data set revealed that PGR expression is indeed correlated with BMI in endometrial cancer [16, 17]. GREB1 is essential for progesterone-driven endometrial decidualisation [18]. Hormone-targeted therapies are a common approach for advanced endometrial cancer and are more effective in patients with progesterone receptor positive tumours [19].…”
Section: Resultsmentioning
confidence: 99%
“…Informed consent was obtained in accordance with a protocol approved by the Washington 151 Corporation, Carlsbad, USA) as described previously (Camden et al 2017 Sigma-Aldrich]). The EPC medium was changed every 48 hours until day six, when the cells were 177 harvested for RNA isolation with the total RNA isolation kit (Invitrogen/Life Technologies, Grand 178 Island, NY) or for protein isolation.…”
Section: Materials and Methods 149mentioning
confidence: 99%